Transient GUS assay based quick screening method of genes cloned in a binary vector in tandem for plant transformation - Khomdram, Shusma; Barthakur, Sharmistha (Annals of Agricultural Research, 2016)
The Escherichia coli Î²-glucuronidase gene (GUS) was used as a gene stacking marker for analysis of genes to be mobilized and expressed in transformed plants. Higher plants lack intrinsic Î²-glucuronidase activity, thus enhancing the sensitivity with which measurements can be made. A gene stacking cassette was constructed in binary vector pBi121 under the control of cauliflower mosaic virus (CaMV) 35S promoter along with a gene encoding transcription factor from wheat WRKY10 before the GUS reporter gene to direct the expression of both the genes in transformed plants through Agrobacterium mediated transformation. After PCR confirmation of cloning, expression of GUS was done which could be observed both in bacterial culture suspension and transiently expressed in explants of Nicotiania tabacum. This quick initial screening using GUS can be performed for cloning more than one gene for further downstream applications. The results confirmed expression of both the genes in tandem in Agrobacterium as well as in plant system and can be used to stack stably more than two genes for manipulating important plant growth and developmental traits.